Morphological characteristics of local rice in Deli Serdang District, North Sumatra, Indonesia - NOVERINA CHANIAGO; IRFAN SULIANSYAH; IRAWATI CHANIAGO; NALWIDA ROZEN (Society for Indonesian Biodiversity, 2022)
Abstract. Chaniago N, Suliansyah I, Chaniago I, Rozen N. 2021. Morphological characteristics of local rice in Deli Serdang District, North Sumatra, Indonesia. Biodiversitas 23: 883-894. The preservation of local rice is essential to preventing genetic drain. In Deli Serdang District, North Sumatra, Indonesia, local rice is in great abundance. A total of 23 Deli Serdang local rice were collected and studied from coastal to highland areas. This study aims to determine the morphological characteristics of 23 local rice genotypes of Deli Serdang and to obtain superior characters to be developed into superior local varieties. A completely randomized design with three replicates was used in this study. Morphological characteristics of 23 local rice genotypes obtained various characters. The culm length was short to very long; culm diameter was thin to thick; the leaf-blade length was long to very long; leaf-blade width was intermediate to broad; culm number was low to high. The auricle, ligule, and collar were almost completely whitish, except for Sijambi yellowish-green and green, 2-cleft acute ligule shape. The harvest age was medium to deep. The grains were white, straw, gold, brown, brown spots, brown lines, and black. The pericarps were white, light brown, red, and black. Most of the organs indicated broad genetic variability having the opportunity to be developed into superior local varieties. All local rice was scattered into five groups based on morphological markers with a similarity of 32.12%.